Impacts of estradiol on PGF2α release and corpus luteum function during early pregnant in beef heifers - Motta, Igor Garcia (2023)
In the first study, the effects of 17βestradiol (E2) or estradiol benzoate (EB) on PGF2α release were studied in bred-non-pregnant and pregnant beef heifers. Thirty-two Nelore heifers, aged between 16 and 18 months, weighing 314 ± 31 kg, and body condition score (BCS) between 3 and 4 were used. The females received an intravaginal P4 device (1g Sincrogest®, Ourofino Saúde Animal) 14 days after timed artificial insemination (TAI) and were randomly assigned in three groups: Control (C, P4 device only); E2 (1 mg E2 + 9 mg P4; Betaproginn®, Boehringer Ingelheim); or EB (1 mg; Sincrodiol®, Ourofino). Blood samples were collected hourly for 8 hours after treatment to measure plasma concentrations of a PGF2α metabolite (PGFM). The P4 device was removed on D22 and pregnancy was diagnosed on D28. The proportion of pregnant heifers did not differ between the control (7/12), E2 (5/10) and EB (5/10) groups. The average PGFM concentration during the 9 hours was greater in E2 group (55.3 ± 10.2) than EB (37.2 ± 4.7) and the control group (25.1 ± 1.1). In addition, luteolysis occurred earlier in the E2 group than in the EB group. Also, in pregnant heifers, 1 mg EB 14 days after TAI did not induce PGF2α release, and only the number of prominent PGFM pulses and maximum concentration were greater than controls. In study 2, Experiment 1, was evaluated the effects of different doses of EB at 13 days after ovulation on the release of PGF2α and the size and function of the corpus luteum in pregnant and non-pregnant heifers. Forty-seven Nelore heifers, aged between 18 and 24 months, weighing 390 ± 35 kg, and body condition score (BCS) between 3 and 4 were used. Estrus was synchronized and heifers were randomly subdivided into non-inseminated or inseminated. Thirteen days after ovulation (D13), the heifers were randomly assigned to three groups to receive 0, 1 or 2 mg of EB. On D13, blood samples were taken at hour 0 (H0) (before treatment) and hourly from H3 to H12 to measure the PGFM. Doppler ultrasonography was performed daily from D13 to D19. Pregnancy was diagnosed on D28. Regardless of the dose, luteolysis was earlier in non-inseminated heifers treated with EB than in the control group (16.3 ± 0.2 vs. 17.3 ± 0.6 days). The proportion of pregnant heifers was lower in the groups treated with 1 mg (50%; 8/16) and 2 mg (29.2%; 7/24) when compared to the control group (90%; 9/10). The average concentration of PGFM during the 10 hours of collection was greater in EB groups treated with 1 mg (46.3 ± 3.6 pg/mL) and 2 mg of BE (46.9 ± 3.3 pg/mL) than in the control group (28.0 ± 1.2 pg/mL) regardless of gestational status. In Experiment 2, the effects of 0 and 1 mg of EB, 13 days after ovulation on the components of the endometrial cascade of PGF2α synthesis in non-inseminated and in pregnant beef heifers were evaluated. Forty Nelore heifers, aged between 24 and 30 months, weighing 437 ± 45 kg, and body condition score (BCS) between 3 and 4 were used. Thirteen days after ovulation, the heifers were randomly assigned to two groups: 0 or 1 mg of EB. Three hours after the treatments, endometrial cytology was performed and samples were subsequently evaluated by qPCR. The abundance of OXTR and PGR was affected by EB treatment, being greater in heifers treated with 1 mg of EB. ESR2 abundance was lower in pregnant heifers, regardless of EB treatment. The abundance of the main enzymes involved in PGF2α release was not affected by EB treatment. Pregnancy status had no influence on IL1-β gene expression, but heifers treated with 1 mg EB had a lower expression compared to heifers in the control group. In conclusion, treatment with 1 or 2 mg EB 13 days after ovulation in beef heifers induces PGF2α release and anticipates luteolysis by one day in non-pregnant heifers.